1998
DOI: 10.2494/photopolymer.11.187
|View full text |Cite
|
Sign up to set email alerts
|

Photo Alignment Materials with High Sensitivity to Near UV Light.

Abstract: We developed new photo alignment materials based on chalconyl structure with high sensitivity to near UV light. Poly(4-methacryloyloxy chalcone), PM4Ch, and its derivatives exhibited good LC alignment upon near TJV exposure. The photoreactivity of chalconyl structure was high because due to longer wavelength of UV absorption. The high sensitivity of PM4Ch, compared with Poly(4'-methacryloyloxy chalcone), PMCh, could be explained by the suppression of isomerization and/or by the alignment capability of the side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 2 publications
0
43
0
Order By: Relevance
“…The peak at 260 nm was assigned to the dimerized moieties of the mesogenic group due to the cycloaddition reaction of the chalcone moiety. 14 The DR values of the peak at 260 nm were positive. This result indicated that the dimerized moieties were aligned parallel to the electric vector of the incident LPUV light.…”
Section: Photoinduced Anisotropy Of Polymer Filmsmentioning
confidence: 99%
See 3 more Smart Citations
“…The peak at 260 nm was assigned to the dimerized moieties of the mesogenic group due to the cycloaddition reaction of the chalcone moiety. 14 The DR values of the peak at 260 nm were positive. This result indicated that the dimerized moieties were aligned parallel to the electric vector of the incident LPUV light.…”
Section: Photoinduced Anisotropy Of Polymer Filmsmentioning
confidence: 99%
“…The peak around 320 nm was assigned to the mesogenic group containing the chalcone derivative with the trans conformation, while the peak around 260 nm in the spectra of the polymer 1 film was attributed to the dimer structure formed by the photoreaction. 14 The photodimerization and photoisomerization are known as a possible photoreaction of the photoreactive molecules like the chalconyl or the cinnamoyl groups. We investigated the photoreaction of the chalconyl groups by FT-IR measurements.…”
Section: Photoreaction Of Polymer Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 The polymers containing chalcone group in the side chain were also frequently studied for application to LC photoalignment layer. 15 The induction mechanism of optical anisotropy is identical with that in polyvinylcinnamate.…”
Section: Introductionmentioning
confidence: 53%